Navigated transcranial magnetic stimulation in preoperative planning for the treatment of motor area cavernous angiomas - Paiva WS (Dove Medical Press, 2013)
Wellingson Silva Paiva,1 Erich Talamoni Fonoff,1 Marco Antonio Marcolin,2 Edson Bor-Seng-Shu,1 Eberval Gadelha Figueiredo,1 Manoel Jacobsen Teixeira11Division of Neurosurgery, Department of Neurology, School of Medicine, University of Sao Paulo, Sao Paulo, Brazil; 2Transcranial Magnetic Stimulation Laboratory, Institute of Psychiatry, School of Medicine, University of Sao Paulo, Sao Paulo, BrazilAbstract: Since the introduction of microscopic techniques, radical surgery for cavernous angiomas has become a recommended treatment option. However, the treatment of motor area cavernous angioma represents a great challenge for the surgical team. Here, we describe an approach guided by frameless neuronavigation and preoperative functional mapping with transcranial magnetic stimulation (TMS), for surgical planning. We used TMS to map the motor cortex and its relationship with the angioma. We achieved complete resection of the lesions in the surgeries, while avoiding areas of motor response identified during the preoperative mapping. We verified the complete control of seizures (Engel class 1A) in the patients with previous refractory epilepsy. Postsurgery, one patient was seizure-free without medication, and two patients required only one medication for seizure control. Thus, navigated TMS appears to be a useful tool, in preoperative planning for cavernous angiomas of the motor area.Keywords: neurosurgical procedures, brain mapping, neuronavigation